Evaluation of the Involvement of Heme Oxygenase-1 Expression in Discoid Lupus Erythematosus Lesions - Paolo Fagone; Eliana Piombino; Katia Mangano; Rocco De Pasquale; Ferdinando Nicoletti; Rosario Caltabiano (MDPI AG, 2023)
Discoid lupus erythematosus (DLE) is a chronic autoimmune disease that primarily affects the skin, causing red, scaly patches that may be disfiguring and can cause permanent scarring. This study aimed to investigate the potential clinical and therapeutic applications of heme oxygenase-1 (HMOX1) in the context of DLE. Immunohistochemical staining and bioinformatics analysis were performed on skin biopsy samples from DLE patients to examine the levels of HMOX1 and to correlate with markers of inflammation. Our study revealed a negative correlation between HMOX1 levels and the inflammatory status of DLE lesions, as well as an inverse correlation between HMOX1 levels and the infiltration of M1 macrophages and activated mastocytes. These findings suggest that HMOX1 plays a crucial role in the regulation of inflammation in DLE and could be a potential therapeutic target and biomarker for DLE.